Fabrication and characterization of sputtered ZnO thin film for head-disk interface application - Yu, Xue. (2011)
The increasing of hard disk capacities requires a decreasing flying height of hard disk drive slider. The active-head slider technology for hard disk drive is one of the most promising means to decrease flying height. In this study, ZnO thin films were deposited on Si and Al/SiO2/Si substrate using RF Magnetron sputtering system. Then the effects of the process parameters on the property of ZnO films were investigated for various RF powers, working pressures and O2/(O2+Ar) gas ratios. The preferable parameters to produce high quality ZnO film will be presented. Two groups of piezoelectric cantilevers were fabricated to measure the piezoelectric coefficient of the fabricated ZnO film. The ZnO film in cantilever 1 was produced without oxygen and cantilever 2 produced under the preferable parameters found previously. The details steps to fabricate such cantilevers will be presented in this report. Laser Doppler vibrometer (LDV) was used to investigate the piezoelectric coefficients (d31) of ZnO film in each cantilever. The piezoelectric coefficients (d31) of ZnO film were found to be 0.166 pm/V and 3.2 pm/V respectively.